Ethical priority of the most actionable system of biomolecules: the metabolome. Issue 2 (23rd October 2019) - Lewis, Cecil M.; McCall, Laura‐Isobel; Sharp, Richard R.; Spicer, Paul G.
Abstract: The metabolome is a system of small biomolecules (metabolites) and a direct result of human bioculture. Consequently, metabolomics is well poised to impact anthropological and biomedical research for the foreseeable future. Overall, we provide a perspective on the ethical, legal, and social implications (ELSI) of metabolomics, which we argue are often more alarming than those of genomics. Given the current mechanisms to fund research, ELSI beyond human DNA is stifled and in need of considerable attention.